Structural contradictions in control system by enterprise as function of associate administrative decisions - Kalyuzhna, N.; Golovkova, К. (Національний університет "Львівська політехніка", 2013)
The key role of organizationally-functional structure improvement of management is reasonable in the increase of efficiency of preparation processes, acceptance and realization of administrative decisions on an enterprise. The algorithm of structural exposure contradictions is offered in control system by an enterprise. The morphological matrix of description of structural contradiction as functions of associate administrative decisions is formed. Sources 22.
Keywords: control system; administrative decision; algorithm; morphological matrix; structural contradiction